2022
DOI: 10.3847/1538-4357/ac58f6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Spectra of the Blazars Mrk 421 and Mrk 501 at TeV Energies Seen by HAWC

Abstract: The High Altitude Water Cherenkov (HAWC) Gamma-Ray Observatory surveys the very high-energy sky in the 300 GeV to >100 TeV energy range. HAWC has detected two blazars above 11σ, Markarian 421 (Mrk 421) and Markarian 501 (Mrk 501). The observations are comprised of data taken in the period between 2015 June and 2018 July, resulting in ∼1038 days of exposure. In this work, we report the time-averaged spectral analyses for both sources, above 0.5 TeV. Taking into account the flux attenuation due to the extraga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…These are two extensively studied extragalactic sources and the brightest in the teraelectronvolt band. Both sources have been significantly detected by HAWC above 300 GeV up to 10 TeV (Albert et al 2022) and by Fermi-LAT between 100 MeV and 1 TeV . For the HAWC data set, 1343 days of data were used, taken between 2015 June and 2019 June ).…”
Section: Data: Hawc and Fermi-latmentioning
confidence: 93%
See 4 more Smart Citations
“…These are two extensively studied extragalactic sources and the brightest in the teraelectronvolt band. Both sources have been significantly detected by HAWC above 300 GeV up to 10 TeV (Albert et al 2022) and by Fermi-LAT between 100 MeV and 1 TeV . For the HAWC data set, 1343 days of data were used, taken between 2015 June and 2019 June ).…”
Section: Data: Hawc and Fermi-latmentioning
confidence: 93%
“…To avoid an overestimation of the intrinsic flux, each source's lowest energy flux point observed by HAWC (Albert et al 2022) is used as a guide; observed Mrk 421 and Mrk 501 flux points at an energy of 830 and 750 GeV, respectively, are de-absorbed according to Franceschini et al (2008) model. These de-absorbed flux points are included in the set of flux points obtained from the Fermi-LAT analysis described above, and altogether are used to fit a physically motivated emission model with Naima: a python software that calculates the nonthermal emission from a leptonic or hadronic population of particles, Zabalza (2015).…”
Section: Intrinsic Spectra: Fermi-lat and Naimamentioning
confidence: 99%
See 3 more Smart Citations